Muscle Atrophy Around the Hip Joint in Patients with Femoral Neck Fracture is Associated with Postoperative Walking Ability - Hyonmin Choe MD, PhD; Takahiro Yoneda MD; Masatoshi Oba MD, PhD; Koki Abe MD, PhD; Hiroyuki Ike MD, PhD; Ken Kumagai MD, PhD; Naomi Kobayashi MD, PhD; Yutaka Inaba MD, PhD (Geriatric Orthopaedic Surgery & Rehabilitation)
Introduction Patients with femoral neck fractures (FNF) have reduced walking ability owing to muscle weakness. Preoperative muscle volume and quality may have an association with prolonged rehabilitation and can be useful to predict the postoperative walking ability in patients with FNF. This study aimed to compare the muscle volume and computed tomography (CT)-assessed density around the hip joint in patients with FNF with patients having hip osteoarthritis (HOA) and assess the association of these measurement with postoperative walking ability. Materials and Methods This retrospective observational study included 15 patients with FNF and 15 with unilateral HOA who were matched for age, sex, and osteoporosis medication. Muscle volume and CT-assessed density of the gluteus maximus, gluteus medius, gluteus minimus, iliacus, psoas major, rectus femoris, and rectus abdominis on the unaffected side were measured three-dimensionally using 3D Slicer software with preoperative CT data. The associations of muscle measurement with patient background, load to FNF (measured using the finite element method), and pre- or postoperative walking ability were assessed. Results Muscle volume of gluteus maximus, CT-assessed density of all muscles, and femoral strength were significantly lower in the FNF group than in the OA group ( P < .01, P < .01, and P = .04, respectively). Muscle volume showed a moderate-to-strong correlation with body mass index (r = 0.66-0.81) and FNF load (r = 0.51-0.70), and CT-assessed density showed a moderate correlation with serum nutritional markers (r = 0.33-0.60). Postoperative walking ability was significantly correlated with the muscle volumes of iliacus and gluteus maximus (r = 0.40 and 0.49) and CT-assessed density of all muscles (r = 0.47-0.64). Conclusion Muscle volume and CT-assessed density significantly correlated with femoral bone strength, serum total protein levels, and pre- and postoperative walking ability. These findings suggest that muscle CT analysis around the hip joint may serve as a valuable tool for assessing musculoskeletal status in patients with FNF.